2002
DOI: 10.1108/10662240210422549
|View full text |Cite
|
Sign up to set email alerts
|

Web usage, advertising, and shopping: relationship patterns

Abstract: Web sales reached over 30 billion dollars in the year 2001. This study explores the differences between heavy, medium, and light Web users in terms of their beliefs about Web advertising, attitudes toward Web advertising, purchasing patterns, and demographics. They lead to a more positive attitude toward Web advertising, which likely leads to more frequent Web purchasing and higher dollars spent on these purchases, suggesting marketers should consider consumer Web usage in their targeting efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 19 publications
5
68
0
5
Order By: Relevance
“…Recent studies of online advertising have also shown a positive relationship between attitude and purchase intentions and between attitude and behavior, such as the likelihood of buying, online visitations, and online shopping frequency (Bruner and Kumar, 2005;Karson and Fisher, 2005;Korgaonkar and Wolin, 2002;Stevenson et al, 2000;Wang et al, 2009;Wolin et al, 2002). Previous studies have included purchase intentions as a key indicator of the success of online advertisements (Brown and Stayman, 1992;Moe and Fader, 2004;Raney et al, 2003).…”
Section: Relationships Among Advertisement Responses Website Attitudmentioning
confidence: 91%
“…Recent studies of online advertising have also shown a positive relationship between attitude and purchase intentions and between attitude and behavior, such as the likelihood of buying, online visitations, and online shopping frequency (Bruner and Kumar, 2005;Karson and Fisher, 2005;Korgaonkar and Wolin, 2002;Stevenson et al, 2000;Wang et al, 2009;Wolin et al, 2002). Previous studies have included purchase intentions as a key indicator of the success of online advertisements (Brown and Stayman, 1992;Moe and Fader, 2004;Raney et al, 2003).…”
Section: Relationships Among Advertisement Responses Website Attitudmentioning
confidence: 91%
“…In an online setting, various studies have established the mediating role of attitude in the relationship between site stimuli and online purchase intention (e.g. Korgaonkar & Wolin, 2002;Rasty, Chou, & Feiz, 2013;Stevenson, Bruner, & Kumar, 2000;Wu et al, 2008).…”
Section: Attitudinal Responses: Attitudes Toward Advertising (Ata) Anmentioning
confidence: 99%
“…Mehta and Sivadas (1995) found newsgroup users held negative attitudes toward Internet advertising, but the business executives researched by Ducoffe (1996) did not find Internet advertising either irritating or annoying. Korgaonkar and Wolin (2002) also found that Internet advertising is honest, believable, entertaining and enjoyable, informative, and as well as helpful also. Gordon and De Lima-Turner (1997) studied advertising on the Internet from the perspective of a social contract between advertisers and Internet users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers examining the Internet purchaser fall within the stream identified earlier. The Internet shopper has been found to be older and/or of higher income (Donthu and Garcia, 1999;Korgaonkar and Wolin, 2002), slightly more likely to be male (Korhankar and Wolin, 1999;Andrews et al, 2007) and less risk averse Korgaonkar, 2003, Korganorkar andWolin, 1999). There is also evidence that the Internet shopper is convenience oriented (Korgaonkar and Wolin, 1999), innovative and variety seeking (Donthu and Garcia, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%